INFLUENCE OF BASES OF REMOVABLE DENTURE STRUCTURES ON MICROBIOLOGICAL STATUS OF ORAL CAVITY (LITERATURE REVIEW) - Рожко, С. М.; Куцик, Р. В.; Палійчук, І. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Normal microflora of oral cavity represents a unique system of microorganisms that form normal microbiocenosis, which plays an important role in human health and diseases. All diseases of oral cavity associated with disturbances of the resident microflora under influence of various factors, the species composition of the microflora of oral cavity is normally fairly constant. Together with this amount of microbes can fluctuate. The formation of microflora can be influenced by many factors, such as: the state of the mucous membrane of oral cavity, temperature, pH, oxidation-reduction processes in oral cavity, secretion of saliva, its composition, condition of teeth, composition of food, oral hygiene condition, normal function of salivation, chewing, swallowing, natural resistance of human body.